PENINGKATAN PEMAHAMAN GURU PAI TENTANG PENILAIAN KURIKULUM 2013 OLEH PENGAWAS MELALUI KEGIATAN WORKSHOP DI KECAMATAN LUBUK DALAM - Zulkarnain Zulkarnain (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
From the preliminary observational data made by the researchers before conducting the workshop, more or less 99% did not understand the 2013 curriculum assessment system. This was due to (1) the teacher did not have a teacher's PAI handbook and student handbook because the school focused more on thematic books (2) teachers reluctant to change the mindset of a scientific approach, along with their learning models, (3) teachers are reluctant to understand the concept of assessment which is very complicated and is considered to increase the work of teachers such as providing attitude assessment instruments and others (4) teachers lack mastery of computer use (5) teachers assume schools have provided assessment application. In this study researchers used the Supervisory Action Research (PTKP) method. The School Action Research was conducted on PAI teachers assisted by researchers who were in Lubuk Dalam sub-district of Siak district. The study aims to improve teacher competency in carrying out the 2013 curriculum assessment process. This research was conducted in the second semester of the 2017/2018 academic year for approximately three months from January to March 2018.